Comparison of the sample preparation methods worked out for the examination of the element content of wine - Fekete, István; Andrási, Dávid; Kovács, Béla (Acta Agraria Debreceniensis, 2012)
The examination of the potentially toxic elements content of the wines is not easy task, because the most elements are in little concentration (mg kg-1 or μg kg-1) in the wine and the wines contain great amount of organic matrix. The efficient sample preparation is essential for the accurate determination of element content. The eim of our research was to determine which sample preparation method will be the most efficient in examination of wines with ICP technology. The examined wine sample was a 2008 Chardonnay from the Eger wine region. We did the sample preparation and analysis examination in University of Debrecen, Centre for Agricultural and Applied Economic Sciences, Institute of Food Science, Quality Assurance and Microbiology. We did the analysis examinations with ICP- MS (inductively coupled plasma mass spectroscopy). We always did the sample preparations and the examinations in three times rehearsal. The applied sample preparation methods: dilution with distilled water, open digestion and microwave digestion. We were able to measure B, Al, Mn, Fe and Zn with only dilution and open sample preparation. In the smaller quantity present Sr and Ba were measurable in the wine in the case of all three methods well. We were able to measure the Co with dilution and open digestion method, while Cr, Ni, and Te with only dilution method. In the case of arsenic we were not able to measure reliable result with dilution and open digestion method because of organic matrix and other components (alcohols, monosaccharides, polysaccharides, polyalcohols and inorganic salts). On the whole we are able to say that in the case of certain elements (B, Mn, Fe, Zn, Sr, Ba) the open digestion and dilution sample preparation is applicable well, however, in the case of certain elements (As, Al, V, Cr, Se, Mo, Cd, Hg, Pb) we have to develop the methods. It may be development of one of the way, if we develop sample preparation methods to examined element specifically and not to wine generally.